Comparison of Shielding Capacity of Self-produced nano-size and micro-size molybdenum shielding sheet with diagnostic X-ray imaging system - Kim, Dae Ho; Kim, Sang Hyun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Lead is widely used as a material for shielding radiation. but lead is harmful and expensive to dispose of. shielding materials that can be used in place of lead are bismuth (Bi), tungsten (W) and molybdenum (Mo). as these materials become smaller in size, the surface area of the entire material increases dramatically, resulting in nano sized materials having different physical properties therefore, the purpose of this study is to use molybdenum, which is harmless to the human body as a material to replace lead, to produce shielding sheets according to particle size and to compare shielding capacity. Methods/Statistical analysis: Nano-sized molybdenum and micro-sized molybdenum particle was analyzed using TEM equipment. molybdenum was used to fabricate micro and nano sized shielding sheets and to analyze the shielding performance according to energy band. shielding ability of the nano-sized molybdenum shielding sheet and the micro-sized molybdenum shielding sheet was compared according to the kV range. the low energy range was set from 41kV to 70kV, and 5 times were measured in the range of 41-50, 51-60, 61-70 with increasing kV by 1. the Middle Energy Range was set from 71kV to 100kV, and the measurement was repeated five times in the range of 71-80, 81 -90, 91-100 with increasing kV by 1 Findings: In the low-energy area (41-70kV), micro-shields had 81% higher transmittance than nano shielding. In the middle energy area (71-100kV), micro shielding had an 18% higher transmission rate than nano shielding. In high-energy areas (101-140kV), the transmittance rate of micro and nano shielding was the same. Improvements/Applications: As a result of comparing the shielding ability of the molybdenum of the micro particle size and the nano particle size, the shielding ability of the nano particle size molybdenum sheet showed better shielding ability in the low energy region.